2007
DOI: 10.1590/s0100-67622007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of QTLs related with wood quality and developmental characteristics in hybrids (Eucalyptus grandis x Eucalyptus urophylla)

Abstract: -The present work aimed to characterize and identify QTLs for wood quality and growth traits in E. grandis x E. urophylla hybrids. For this purpose a RAPD linkage map was developed for the hybrids (LOD=3 and r=0.40) containing 52 markers and 12 linkage groups. Traits related to wood quality and growth were evaluated in the QTL analyses. QTL analyses were performed using chi-square tests, single-marker, interval mapping and composite interval mapping analyses. All approaches led to the identification of similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…Thamarus et al (2004), also found co-located QTL for pulp yield and cellulose content on two different linkage groups in E. globulus, distinct from those presented here (Table 4). Similarly, Rocha et al (2007) found co-located QTL for pulp yield and lignin content in Eucalyptus grandis × E. urophylla. Taken together, these findings confirm suggestions that cellulose content is a useful proxy for pulp yield (Raymond and Schimleck 2002), and that selection for increased cellulose content or pulp yield are likely to result in a reduction in lignin content , which is a favourable outcome for a pulpwood breeding objective.…”
Section: Qtl Locationmentioning
confidence: 82%
See 1 more Smart Citation
“…Thamarus et al (2004), also found co-located QTL for pulp yield and cellulose content on two different linkage groups in E. globulus, distinct from those presented here (Table 4). Similarly, Rocha et al (2007) found co-located QTL for pulp yield and lignin content in Eucalyptus grandis × E. urophylla. Taken together, these findings confirm suggestions that cellulose content is a useful proxy for pulp yield (Raymond and Schimleck 2002), and that selection for increased cellulose content or pulp yield are likely to result in a reduction in lignin content , which is a favourable outcome for a pulpwood breeding objective.…”
Section: Qtl Locationmentioning
confidence: 82%
“…Grattapaglia et al 1996;Verhaegen et al 1997;Thamarus et al 2004;Bundock et al 2008), while fewer studies have published QTL for chemical wood property traits, such as cellulose and lignin content (e.g. Thamarus et al 2004;Rocha et al 2007). Hence, the aims of this study were to locate QTL for chemical and physical wood property traits as well as growth traits in E. globulus and to study the colocation of QTL with previously mapped QTL and candidate genes.…”
Section: Introductionmentioning
confidence: 99%
“…Trabalhos que objetivam o desenvolvimento de mapas-referência e detecção de QTL's têm se baseado na avaliação de pelo menos 200 indivíduos (COSTA & SILVA et al, 2007;ROCHA et al, 2007). Espécies diploides representam diversas espécies vegetais cultivadas (BORÉM, 2001).…”
Section: Resultsunclassified
“…The desired traits vary among plants depending on the plant under study and the interest to a special or specific trait and the pertinent QTLs. QTLs have increasingly been reported in several studies such as plant height Brown et al (2008) Li et al (2015) Xu et al (2017), resistance to diseases Ayala et al (2002) Zhou et al (2015), seed size Zhang et al (2015), grain yield Vikram et al (2016), wood production in trees like Eucalyptus Rocha et al (2007), and higher yield Habyarimana et al (2017) Lu et al (2017).…”
Section: Qtlsmentioning
confidence: 99%